The Effectiveness of Art Therapy on Psychomotor Skills and Visual Memory in Children with Learning Disabilities - Sajadi Dokht Langeroudi, Shiva; Asmaee Majd, Sirvan (Mental Health and Lifestyle Journal, 2026)
Learning disabilities can have extensive impacts on the social, psychological, and behavioral dimensions of children, leading to reduced attention, motivation, and self-esteem. This study aimed to determine the effectiveness of art therapy on psychomotor skills and visual memory in children with learning disabilities in Gilan Province. The study was a quasi-experimental design with a control group. The statistical population comprised children with learning disabilities in reading, writing, and spelling, aged 8 to 12 years, in Gilan Province during the 2024–2025 academic year. From this group, 32 children aged 8, 9, and 10 years were selected using convenience sampling and randomly assigned to experimental (n = 16) and control (n = 16) groups. The experimental group participated in 10 sessions of 60-minute art therapy, while the control group received no intervention. The assessment tools included the Lincoln-Ozeretsky Test of Psychomotor Skills (Lincoln & Ozeretsky, 1923) and the Kim-Carad Visual Memory Test (Kim & Carad, 1977), which provided precise measurement of children’s psychomotor skills and visual memory. Data were analyzed using descriptive statistics and multivariate analysis of covariance (MANCOVA) in SPSS version 26. MANCOVA revealed that art therapy had a significant effect on psychomotor skills (p =.002, F = 11.440) in children, but no significant difference was observed in visual memory (p =.07, F = 1.299). These results align with previous studies and attention and focus models related to learning disabilities, indicating that art-based interventions can enhance children’s motor abilities. This study demonstrates that art therapy effectively improves psychomotor skills in children with learning disabilities.